SCIENCE JOURNALISM WITHIN THE FRAMEWORK OF MEDIA RICHNESS THEORY - Husni Refat Husni Abd Al-Elah, Shukria Kawkaz Al-Saraj (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study investigates the nature of the relationship between science journalism and the Theory of Media Richness by introducing a theoretical framework that suggests a model for the parts of the richness and their scientific degree, in which it allows the user to employ it in order to provide the scientific medium with exceptionally adequate content on the publication platforms, social media, journals and such. It serves the role of the scientific media message and also responds to the demands of the people who want this specialized journalism, which is deeply connected with human existence.